2017
DOI: 10.3390/ijms18102052
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Photoaging Effect of Jeju Putgyul (Unripe Citrus) Extracts on Human Dermal Fibroblasts and Ultraviolet B-induced Hairless Mouse Skin

Abstract: Ultraviolet (UV) radiation stimulates the expression of matrix metalloproteinases (MMPs) and inflammatory cytokines. These signaling pathways participate in the degradation of the extracellular matrix and induce inflammatory responses that lead to photoaging. This study evaluated the antioxidant activity and the effect on MMPs and procollagen of putgyul extract in vitro. The anti-photoaging activity of putgyul extracts was estimated in vivo using hairless mice (HR-1). The putgyul extracts reduced MMP-1 product… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 42 publications
1
12
0
Order By: Relevance
“…Studies have shown that certain dietary factors can improve the signs of skin aging [9,25]. Accordingly, the attention of the cosmetic industry has recently focused on numerous crude herbal extracts to prevent skin aging [26,27]. In this report, and for the first time, we aimed to determine the anti-photoaging activity of WHS and elucidate the associated molecular mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that certain dietary factors can improve the signs of skin aging [9,25]. Accordingly, the attention of the cosmetic industry has recently focused on numerous crude herbal extracts to prevent skin aging [26,27]. In this report, and for the first time, we aimed to determine the anti-photoaging activity of WHS and elucidate the associated molecular mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…RT-qPCR was performed by modifying a previously published protocol (25) to determine the effect of FRB, FSB and FSC (40 mg/kg) on MMPs (MMP-2,9,3 and 13) and inflammation-associated cytokines including TNF-α, COX-2, iNOS, IL-6 and IL-1β. Total cellular RNA was extracted from skin tissue using the phenol-chloroform method using RNAzol (Tel-Test, Inc., Friendswood, TX, USA).…”
Section: Methodsmentioning
confidence: 99%
“…In addition, the increase in matrix metalloproteinase (MMP) activity in response to ROS production results in the destruction of the structure and function of the extracellular matrix (ECM) via collagen degradation (24). UV exposure also stimulates the production of cyclooxygenase-2 (COX-2), which aggravates skin inflammation by catalyzing the synthesis of prostaglandin E2 and inducing the expression of inducible nitric oxide synthase (iNOS), which may result in skin inflammation (25).…”
Section: Introductionmentioning
confidence: 99%
“…The mechanisms of UV-induced skin damage involve inflammation by inflammatory cytokines and collagen degradation by collagenases [ 6 ]. Among the inflammatory cytokines, proinflammatory cytokines such as interleukin (IL)-1β and tumor necrosis factor alpha (TNF-α) stimulate the generation and accumulation of ROS and, furthermore, increase the expression of matrix metalloproteinases (MMPs), which accelerate structural and functional destruction of the extracellular matrix (ECM) and lead to collagen disruption [ 7 ].…”
Section: Introductionmentioning
confidence: 99%